2012
DOI: 10.2308/jiar-10212
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mandatory IFRS Adoption on Accounting Quality: Evidence from Australia

Abstract: Following the mandatory implementation of International Financial Reporting Standards (IFRS) in Australia as of January 1, 2005, this study examines its impact on accounting quality by focusing on three perspectives: (1) earnings management, (2) timely loss recognition, and (3) value relevance. Using four years of adoption experience since the mandate was first made effective in Australia for a wide range of accounting-based metrics and market-based information, we find that the mandatory adoption of IFRS has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
91
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 47 publications
13
91
2
2
Order By: Relevance
“…International Financial Reporting Standards (IFRS), formerly known as International Accounting Standards (IAS), was issued to achieve the objective of preparing high quality international financial reporting standards. A number of studies have shown that the IFRS convergence can improve the quality of accounting information, one of which is shown by a decrease in earnings management in some countries (Capkun et al, 2007, Liu and Liu, 2007, Barth et al, 2008Chen et al, 2010, Chua et al, 2012and Kargin 2013.…”
Section: Introductionmentioning
confidence: 99%
“…International Financial Reporting Standards (IFRS), formerly known as International Accounting Standards (IAS), was issued to achieve the objective of preparing high quality international financial reporting standards. A number of studies have shown that the IFRS convergence can improve the quality of accounting information, one of which is shown by a decrease in earnings management in some countries (Capkun et al, 2007, Liu and Liu, 2007, Barth et al, 2008Chen et al, 2010, Chua et al, 2012and Kargin 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Landsman et al 2012;Chua et al 2012;Brochet et al 2013). However, despite these widespread studies within advanced and developed markets such as European Union (EU) countries and Australia, little research has directly addressed the impact of IFRS adoption on the financial market and quality of financial reporting in an emerging market.…”
Section: Introductionmentioning
confidence: 99%
“…Studies find that IFRS adoption or convergence is associated with accounting quality in Australia (Chua et al, 2012;Elias, 2012) and the France (Zéghal et al, 2011). Adopting IFRS affects the financial position of a publicly reporting accounting entity.…”
Section: Effects Of Adopting Ifrs On Financial Statements and Accountmentioning
confidence: 99%
“…Accounting studies on IFRS and its adoption vary by aim and objective. While some illustrate a specific international standard (e.g., Monday, 2009), some others examine the effect of IFRS adoption and convergence on accounting quality (e.g., Barth et al, 2008;Chua et al, 2012;Elias, 2012;Zeghal et al, 2012) as well the quality of financial statement information (Iatridis, 2010). Other studies investigate the international politics of accounting standards (e.g., Königsgruber, 2010;Posner, 2009Posner, , 2010 and IFRS harmonization (e.g., Ramanna, 2013 1 ) and their relevance (Alali and Foote, 2012;Tyrrall et al, 2007).…”
Section: Introductionmentioning
confidence: 99%